The effect of postoperative pain on comfort in patients undergoing abdominal surgery: The effect of postoperative pain on patient comfort - Soysal, Ganime Esra; Çelebi, Ebru (Journal of Surgery and Medicine, 2024)
Background/Aim: Postoperative pain management aims to reduce pain intensity and improve patient comfort. This study was conducted to investigate the effects of postoperative pain on the well-being of patients undergoing abdominal surgery. Methods: This research was designed as a prospective, descriptive study. The study was conducted on 94 patients who underwent abdominal surgery in general surgery. Patients over 18 years of age, who volunteered to participate in the study and who did not need intensive care were included in the research. Postoperative pain and comfort levels of the patients were analyzed. Descriptive information from the patients was used in the first part of the study and the Perianesthesia Comfort Questionnaire (PCQ) was used in the second part. The visual pain scale (VAS) was used to assess pain. Results: The mean age of the patients was 54.7 (15.7) years; 54.3% of the patients were male; 76.6% were smokers; and the mean body mass index was 29.3 (6.3). Half of the patients underwent open and half underwent laparoscopic surgery, with 90.4% receiving general anesthesia. Patients were hospitalized an average of 3.5 (3.3) days after surgery. Patient comfort was at a good level, according to the PCQ. Whether they received local or general anesthesia did not affect their PCQ scores; however, pain was less in patients who received local anesthesia. Fasting time before surgery did not affect mean PCQ scores, but patients who fasted longer before surgery reported less pain. There were no differences in patients' mean scores on the PCQ scale and pain scores. The correlation between the mean PCQ and pain scales showed no significant relationship (r=-0.073, P=0.485). Conclusion: The absence of a significant correlation between the mean PCQ scale and the pain scale indicates no meaningful association between these variables.